Professionals of family health team professionals against gestacional syphilis in a municipality of northeast Brazil - Andrade, Ana Fatima Souza Melo de (2021)
This study had as objective to evaluate the care regarding syphilis provided by the professionals of the family health teams during prenatal consultations. For this purpose, a structured questionnaire was applied to physicians and nurses working in the health units located in the urban and rural areas of the municipality of  Nossa Senhora do Socorro, in Sergipe, and the results presented using simple descriptive statistics. It was found that 76.2% of the interviewees use the Pregnant Women's Manual during prenatal consultations, adequately recognizing each stage of the disease and the drug therapy to be instituted, but treatment is not started immediately due to a lack of medication in the unity. The interviewees (81%) carried out an active search of pregnant women who were absent from prenatal consultations, but 52.4% presented a strategy to attract their partners. It is concluded that the health professionals against syphilis have the knowledge, but they can not act in an effective way, making it necessary to discuss the knowledge and performance of these professionals, guaranteeing access to training. The need for improvements by health management is also emphasized in order to make the municipality's approach to syphilis more specific and qualified, increasing the chances of eradicating the disease.